KANDUNGAN KARBOHIDRAT DAN KADAR ABU PADA BERBAGAI OLAHAN LELE MUTIARA (Clarias gariepinus B) - Mei Sulistyoningsih; Reni Rakhmawati; Amalia Setyaningrum (Universitas PGRI Semarang, 2019)
The purpose of this study was to determine and study the techniques of tonic immobility, rectal temperature and meat moisture content of broilers. The subjects in the study were 100 unsex DOCs. The design used in this study was Complete Random Injection (CRD) with a 3 x 2 factorial pattern with herbal herbal factorial as many as 3 levels, while factor B treated 2 times with 4 replications, each replication of 4-5 broiler chickens. In this case J (2%) C1: feed commercial ration + ginger 2% + light 1L: 3D, J (2%) C2: feed commercial ration + ginger 2% + light 1L: 2D, K (0.2%) C1: feed commercial ration + turmeric 0.2% + light 1L: 3D, K (0.2%) C2: feed commercial ration + 0.2% turmeric + light 1L: 2D, S (3%) C1: feed ration commercial + bay leaves 3% + light 1L: 3D, S (3%) C2: feed commercial rations + leaves greetings 3% + light 1L: 2D. The research variables studied were the technique of tonic immobility, rectal temperature and broiler meat moisture content. The data obtained were then analyzed using variance (ANOVA) with a level of 5%, the results showed no significant effect (P> 0.05) of the six techniques on incompetence and energy intensity, there was a significant effect (P <0.05). ) the six faces of broiler meat water content.